The Use of Cloze Test To Test Reading Comprehension of Non-English Department Students - Sri Sukarni (Faculty of Culture, Management, and Business Universitas Pendidikan Mandalika (UNDIKMA), 2021)
This research aimed to describe the result of the non-English department students’ reading comprehension tested by using cloze test and the effect of using cloze test on non-English department students’ achievement on reading comprehension. This research is classified into pre-experimental research that used one group pre-test and post-test design. The population of this research is the non-English department students in the academic Year 2020/2021 with a total number of 107 students. The researcher used non-probability sampling type purposive sampling technique and there were 44 students taken as samples. The test is the instrument in this research. Data are taken from the result of pre-test and post-test then analyzed by using statistical technique. The analysis is used to find the significant difference in the students’ reading comprehension ability before and after the use of cloze test. In this research, the researcher used paired sample t-test through SPSS 17.0 to analyze the data. Based on data analysis, the mean score of the pre-test was 46.86 categorized as poor whereas the mean score of the post-test was 65.61 categorized as average to good. The mean score of the pre-test 46.86 smaller than 65.61 mean scores of the post-test. It meant that there was a difference mean score of students’ reading comprehension between the pre-test and post-test. This finding showed there was a different score before and after giving treatment. The result of paired samples t-test analysis showed the significance value Sig. (2-tailed) < alpha (0.000 < 0.05). Therefore, the alternative hypotheses which stated that there is an effect of using cloze test on improving non-English department students’ reading comprehension is accepted. It is concluded that there was an effect of cloze test on improving non-English department students’ reading comprehension.